Organic products quality: vegetable growers perception at an Ecological Fair in Porto Alegre – RS - Valent, Joice Zagna; Tisott, Sirlei Tonello; Schmidt, Verônica; Valent, Vinicius Dornelles (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The use of sustainable agricultural practices promotes natural resources conservation. Specifically, organic foods production stands out among these actions. In this context, the theoretical framework used addressed the agroecological foods production, cooperation on organic agriculture and the perception of quality in organic foods production. Thus, the overall goal was to identify quality parameters adopted by farmers at an Ecological Fair in the city of Porto Alegre, Rio Grande do Sul. This is an applied type research and classified as exploratory with quantitative and qualitative approaches for data processing. The results showed that, for most farmers, a vegetable quality is linked only to organic production. To ensure quality, we emphasize that care must be taken throughout in production chain main links.